Victorian medicine and popular culture - Penner, Louise; Sparks, Tabitha (Science and culture in the nineteenth century ;, 2015)
This collection of essays explores the rise of scientific medicine and its impact on Victorian popular culture. Chapters include an examination of Dickens's involvement with hospital funding, concerns over milk purity and the theatrical portrayal of drug addiction, plus a whole section devoted to medicine in crime fiction.